The Accumulation of Radon Gas in Shophouses: Case Study of Using Concrete with Fly Ash and Phosphogypsum Additives as Building Materials - Srisuwan, Touchaphong (International Journal of Building, Urban, Interior and Landscape Technology, 2025)
Radon is a ubiquitous radioactive noble gas which cannot be detected by any human senses. Moreover, it is known to be the leading cause of lung cancer among non-smokers. Soil is the main source of radon, although another major source of indoor radon is derived from building materials, particularly building materials which are by-products from industrial processes containing relatively high concentrations of radium (such as fly ash and phosphogypsum). These building materials produce more radon gas than the others. This research is divided into two parts. The first part focuses on radon-exhalation rates from cementitious materials which contain variations of fly ash (FA) and phosphogypsum (PG). The second part focuses on the study of the concentrations and distributions of radon in shophouses, one of the most popular residential building types in Thailand, which use fly ash and phosphogypsum as an additive in cement. From the first part, the results from measuring radon concentration in closed test chambers by using a pulse-counting ionization chamber radon gas monitor (Atmos 12 dpx) show that the radon exhalation rate is significantly increased when more fly ash is added (from 40 to 60% in concrete); whereas, a clearly exponential correlation is found between radon exhalation rate and phosphogypsum content. From the second part, the CFD simulations show that, in the case of using 50% PG additive, the interior partitions in shophouses affect the radon concentration level and this noble gas accumulates in areas of poor ventilation, which could reach 648.10 Bq/m3 (higher than the average world value of 39 Bq/m3), resulting in the exceedance of the annual effective dose of 16.33 mSv/y.